The Substitution of Different Concentration of Okara Flour in Brownies Formulation Added of Flaxseed (Linum usitatissimum) as Low-Gluten Healthy Food - Walgiyanti, Immas; Mahardika, Anggara; Murti, Paulus Damar Bayu (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2024)
A tofu factory produces relatively 500 kg of pulp which which have not been widely used. Therefore, this research was conducted with the aim of utilizing the remaining processed waste in the form of dregs from the harmonious processing of tofu which is quite abundant in Bandungan District, Semarang Regency. Tofu/okara waste contains various nutrients such as minerals, calcium, potassium, iron, antioxidants, and isoflavones. Substitution of okara flour mixed with flaxseed, which is a grain that contains biologically active nutrients, including omega-3, fatty acids, dietary fiber, and protein, will produce a food product in the form of low-gluten and high-fiber brownies. Consumer acceptance of color, unpleasant fragrance, soybean fragrance, sweet taste, texture, and preference was measured using an experimental research method using a RAL method with four treatments to get the best formulation. Determination of the best formulation was carried out by organoleptic test on 20 panelists and analyzed by a One-way ANOVA test followed by a DMRT test. The results of the scoring test showed that variations in wheat flour formulations and okara flour substitution had a significant effect (p<0.05) on the organoleptic value aspect. Brownies F2 (1:2) is the best formulation with the highest average value (4.75), which contains 12% wet gluten, 4.3% dry gluten, 0.07% protein, and 47.46% fiber. The product brownies with okara flour substitution and additional flaxseed can be an alternative for healthy food that is lower in gluten and high in fiber and can be developed into souvenirs typical of Bandungan.